Happiness In Volleyball: Turkish Sultans League Sample - Işık Afacan, Meltem; Afacan, Ersin (Progress in Nutrition, 2021)
Study Objectives: Happiness is an important emotion for the careers and performances of athletes. For this reason, the research aimed to measure the happiness perceptions of the female athletes playing in the Turkish Sultans Volleyball League. Methods: In accordance with this purpose, interviews were conducted with 18 Turkish volleyball players by using the criterion sampling method, one of the purposive sampling methods.  A questionnaire that involved a personal information form and a semi-structured interview form prepared by the researchers was used as the data collection tool.  In the analysis of qualitative data, descriptive analysis techniques were utilized. Results: The interview form contained a single question that investigated three things giving happiness to volleyball. This question was supported by the question of “why”. When the data was analyzed, it was determined that the main themes that affected the happiness perceptions of the volleyball players were sociological, psychological, economic, and physiological reasons. Conclusion: In conclusion, for Turkish female volleyball players playing in the Turkish Sultans League, happiness is; doing the sport they love in the team they feel belonged to, building a career through quality training thanks to adequate club facilities, working with qualified coaches who are fair, winning matches, and earning money by playing in accordance with their goals, and thus improving their self-confidence, and being physically, and mentally healthy.